2019
DOI: 10.1002/ijc.32299
|View full text |Cite
|
Sign up to set email alerts
|

Survival among solid organ transplant recipients diagnosed with cancer compared to nontransplanted cancer patients—A nationwide study

Abstract: Solid organ transplant recipients (OTRs) have an increased cancer risk but their survival once diagnosed with cancer has seldom been assessed. We therefore investigated cancer‐specific survival among OTRs with a wide range of cancer forms nationally in Sweden. The study included 2,143 OTRs with cancer, and 946,089 nontransplanted cancer patients diagnosed 1992–2013. Hazard ratios (HR) and 95% confidence intervals (CI) were estimated using Cox regression models adjusted for age, sex and calendar year. Median fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
22
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 49 publications
4
22
0
2
Order By: Relevance
“…Prior studies have demonstrated increased rates of cancer‐related mortality in solid organ transplant recipients, as would be expected, including for head and neck cancers, but again most studies have been hampered by the lack of a control group, making survival comparisons difficult . However, two recent studies have utilized cancer databases to compare cancer patients with transplants to those without: each found a higher rate of cancer‐specific mortality for transplant recipient with certain head and neck cancers . The largest study found increased cancer‐specific mortality in oral cavity/pharynx, but not for thyroid; in the present study, we found significantly worse survival in thyroid patients, but we assessed OS, not cancer‐specific mortality, making comparison of findings challenging .…”
Section: Discussionsupporting
confidence: 66%
See 4 more Smart Citations
“…Prior studies have demonstrated increased rates of cancer‐related mortality in solid organ transplant recipients, as would be expected, including for head and neck cancers, but again most studies have been hampered by the lack of a control group, making survival comparisons difficult . However, two recent studies have utilized cancer databases to compare cancer patients with transplants to those without: each found a higher rate of cancer‐specific mortality for transplant recipient with certain head and neck cancers . The largest study found increased cancer‐specific mortality in oral cavity/pharynx, but not for thyroid; in the present study, we found significantly worse survival in thyroid patients, but we assessed OS, not cancer‐specific mortality, making comparison of findings challenging .…”
Section: Discussionsupporting
confidence: 66%
“…The most common posttransplant malignancies include skin cancers, lymphoproliferative disorders, and lung cancer . Several studies have also demonstrated increased risk of head and neck cancers; in particular, oral cavity, oropharynx, and thyroid cancers have been shown to be associated with prior solid organ transplant . While kidneys are the most commonly transplanted—and correspondingly, studied—solid organ, an increased rate of head and neck cancers has also been shown in heart, lung, and liver transplantations …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations